Analisis Kebutuhan Container Yard Pada PT XYZ - Tiffany, Amelia (Jurnal Sistem Transportasi & Logistik, 2023)
This study aims to determine the level of utilization of the container stacking field, the need for the container stacking field, container projections for the next 12 months. The research method used is data projection and calculation formulas for Container Yard Occupancy Ratio, container yard requirements. The result of the research is that the utilization rate of container storage areas increases and decreases every month, but is still sufficient and the utilization rate is still below the effective land area of 70%, but in June 2022 the utilization rate is quite high at 71.45% exceeding the effective land area so that the occurrence of accumulation. The need for a stacking field every month exceeds the available field area. As can be seen in January 2022, the demand for stacking fields is 8,000 m2 while the available field area is 6,727 m2 . The projected demand for container flows in July 2022 to June 2023 has an increase in demand for container flows, which can be seen in the demand in June 2023 of 4025 TEUs while in September 2022 amounted to 3,804 TEUs. In the projected level of field use (CYOR) it can be seen that in July it was 55.81% while in February 2023 it was 64.61%.